Marketing approach to scaling the business of an innovative startup - G. L. Azoev; E. V. Sumarokova; A. N. Kotova (Вестник университета, 2023)
High-tech products and innovative startups are at high risk. Mechanisms of their minimization are an important condition for the commercial success of innovation. This thesis is especially relevant in the period of business scaling. As a key criterion for the commercial success of the scaling, an indicator of the mass of the extracted profit is proposed. For its growth, the decomposition of the profit formula into 3 factors is presented: the capacity of the target market, the market share of the startup, the target profitability of sales. In the proposed approach, the development of a business scaling project for an innovative startup is based on marketing activities that contribute to the growth of these factors. Due to high risks an innovative product does not always have sufficient market capacity, it is often difficult for it to compete for a significant market share, therefore, it is impossible to increase profitability. In this case the project is not filtered by the criterion of potential profit that can be obtained as a result of scaling, and is postponed. For projects that overcome filtering by 3 key components of profit, the planned results of each event, the timing of their implementation, the performers and the necessary budget are determined.